PENANAMAN NILAI- NILAI KARAKTER DALAM PEMBELAJARAN IPS DI SMP NEGERI 3 JEMBER - Sangidatus Sholiha Sangidatus Sholiha (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2021)
Education is an essential trait that cannot be separated to human basic needs. It increases the human’s potential, organizes the way of thinking, and develops better behavior as well as better human characteristic. The development of character values needs to be carried out continuously. Through the implementation of the 2013 curriculum which is competency-based and character building with contextual and thematic approaches, it is expected that students are able to independently use and improve their knowledge and apply character values in their daily behavior. The development of the character values in social studies learning at SMP Negeri 3 Jember has been implemented by social studies teachers. The teacher delivers it in social studies learning activities through three stages; the stages of planning, implementing and holding assessment processing. The obstacle factors revolve around the diverse of the family backgrounds, the big amount of the learning materials with limited time.Keyword : Character, Social Studies Learning